POLIMORFISME GEN GROWTH HORMONE (GH) PADA SAPI LIMURA (GROWTH HORMONE (GH) GENE POLYMORPHISM OF LIMURA CATTLE) - Slamet Diah Vulkandari; Tety Hartatik; Sumadi (Sumadi) (Faculty of Animal Science, Universitas Gadjah Mada, 2013)
The research was conducted to identify Growth Hormone (GH) olymorphism of Limura cattle. The research was conducted in the smallholder at Lancar, Montok and Duko village, Larangan subdistrict in Pamekasan district, East Java Province and Animal Breeding Laboratory of Faculty of Animal Science, Gadjah Mada University in April 2012. Then research used 35 Limura calves and 10 Madura calves (as control). Blood samples for DNA molecular analysis, i.e. DNA isolation with SDS-PK modification method, DNA amplification with PCR method and genotyping with RFLP method. Identification of GH gene polymorphism was conducted by digesting the DNA fragment of 211 bp extended from the fourthintron region (49 bp) to fifth of exon (162 bp) by AluI enzyme. The result indicated that GH gene of Madura cattle was not polymorphic with frequencies of L allele 1.00 and V allele 0.00. The LL genotype of Madura cattle was 1.00. Frequencies ofL and V allele in Limura cattle were 0.91 and 0.09, respectively. Limura cattle indicated polymorphic with genotype LL 0.83and LV 0.17. As a results, GH gene polymorphism was found in Limura cattle with L allele frequencies higher than V allele. Limura cattles population were not deviated from Hardy-Weinberg quilibrium genetic condition.(Key words: Growth Hormone Gene, Limura Cattle, Polymorphism)